Removal of faecal bacteria and nutrients from domestic wastewater in a horizontal surface flow wetland vegetated with Echinochloa pyramidalis - Lekeufack Martin; Fonkou Théophile; Pamo Tedonkeng Etienne; Amougou Akoa (African Journal of Environmental Economics and Management, 2021)
The aim of this study was to evaluate the removal of faecal bacteria and nutrients from domestic wastewater, in surface flow wetlands vegetated with Echinochloa pyramidalis. Horizontal surface flow (HSF) wetlands were fed with primarily treated domestic wastewater at organic loading rates varying from 20.74 to 27.15 g BOD/m2 /day for two consecutive years. Water samples were collected at two weeks interval from the inflow and the outflow of the treatment wetlands for physicochemical and faecal bacteria analyses. Physicochemical parameters with highest removal rates were total suspended solids (TSS, 62-80%), Nitrates (57-73 %) and PO4-3 (57-84 %). Faecal indicators reductions of 1.4 and 0.3 log units (1st year) and 1.15 and 0.65 log units (2nd year) were respectively recorded in the vegetated and the control wetlands. Reductions of total coliforms, faecal coliforms and faecal streptococci were significantly higher in the vegetated wetland than in the non-vegetated control in both seasons of the first year. In the contrary, there was no significant difference in the removal rates of faecal indicators between vegetated wetland and the non-vegetated control during the dry season of the second year. Wetlands vegetated with E. pyramidalis was proven to be continuously efficient in the removal of faecal indicators for the two years of study, with no significant differences between the seasons of the year and between the years.